PTH-058 A Centres Experience Of Setting Up A New Bowel Cancer Screening Centre And Preparing For Bowel Scope. (9th June 2014) - Taggart, N; Batterton, J; Mcguinness, D; Fitzgerald, G; Morton, B; Otoole, P; Subrumanian, S; Haslam, N; Oates, B; Sarkar, S
Abstract : Introduction: The population served by the Merseyside and North Cheshire Programme was 1.7 million based at University Hospitals Aintree was asked to split because of the imminent introduction of Bowel scope. Authorisation for forming of new centre at the Royal Liverpool Hospital (RLH) by central office was granted in the summer 2013 and implementation was required by February 2014. Methods: The Liverpool and Wirral Bowel screening centre (LandW BSC) was formed with a 45% share of the in the population. The service was designed with the aim to run the FOBT service and then introduce the Bowel Scope (BS) as second wave for the serving population of 802, 000. Results: Workforce: The current workforce at the Royal Liverpool (RLH) included 4x BCSP screening colonoscopists of which one became Clinical Director of the centre. The endoscopy service manager supportive for the nursing and operational aspects and the Endoscopy Admin manager supported the administration aspect. There was full managerial backing by the directorate manager. In addition, programme manager, Lead SSP, 3x New SSPs, 4x admin staff were appointed. Collaborations and Engagement: The logistical issues and training of the new SSPs and Admin staff was heavily facilitated by the current Merseyside and Cheshire programme. Engagement and support also included the National Team, CCG, Local QA team and Screening and Immunisation Regional Team. Implementation group representation from all parties. A business was supported by the trust board. The strong collaboration was made with the team from Arrowe Park Hospital (APH). BowelScope: Stategically, new urology centre had spare capacity for 8 lists to include some evenings and weekends sessions at Broadgreen Hospital was identified as good access site for Liverpool. For the Wirral site, APH was identified as the site to deliver bowelscope and for the population would require 4 lists. Eight endoscopists were further identified (6 nurse endoscopists, 1 Fellow and 1 radiographer-also programme manager) as needing accreditation for bowelscope. All mentees were assigned a mentor (3 BCSP colonoscopists) and put on the pre-accreditation course at RLH. Exams were planned over 3, UKdays for all the endoscopists in April 2014. Prior to the exam, all endoscopists, had 2 flexi lists booked with their mentors at RLH as well as ad-hoc sessions to help with MCQ. Outcome: The LandW BCSC got approval by national office in Jan 2014 with a go live date in Feb to take over FOBT service. Bowelscope is planned for September 2014. Conclusion: The setting up of a new centre in such a short period of time was extremely challenging but successful due to good team work, planning and collaboration. Disclosure of Interest: None Declared.